Qualitative and Quantitative Methods in Libraries Journal Special Issue: Bibliometrics and Scientometrics - Welsh, Teresa S. (Qualitative and Quantitative Methods in Libraries, 2017)
Numerous papers and presentations related to bibliometrics have been presented at the International QQML conference each year. This special issue of QQML Journal contains selected papers representing a variety of bibliometric research methodologies.